The Internal Structure of Yellow Cuboid Diamonds from Alluvial Placers of the Northeastern Siberian Platform - Alexey Ragozin; Dmitry Zedgenizov; Konstantin Kuper; Viktoria Kalinina; Alexey Zemnukhov (Crystals, 2017)
Yellow cuboid diamonds are commonly found in diamondiferous alluvial placers of the Northeastern Siberian platform. The internal structure of these diamonds have been studied by optical microscopy, X-Ray topography (XRT) and electron backscatter diffraction (EBSD) techniques. Most of these crystals have typical resorption features and do not preserve primary growth morphology. The resorption leads to an evolution from an originally cubic shape to a rounded tetrahexahedroid. Specific fibrous or columnar internal structure of yellow cuboid diamonds has been revealed. Most of them are strongly deformed. Misorientations of the crystal lattice, found in the samples, may be caused by strains from their fibrous growth or/and post-growth plastic deformation.